Indian diabetic risk score as a screening tool for assessment of diabetes in urban and rural areas in Andhra Pradesh - Sri, P. K. S. S. Usha; Rao, B. T.; Naidu, S. Appala; Mokshanand, K.; Lakshmi, N. Naga; Keerthi, M. Divya (International Journal Of Community Medicine And Public Health, 2022)
Background: Diabetes mellitus is a major public health problem in Andhra Pradesh and Indian diabetes risk score (IDRS) is a cost-effective tool for screening of undiagnosed diabetic individuals in the community. The objectives of this study were to assess the sensitivity and specificity of IDRS method as a screening tool in community as well as to determine the importance of stress scale in relation with diabetes. Methods: This cross-sectional study was conducted from April 2022 to May 2022 among 18 years and above residing in select areas of Prakasam and Visakhapatnam districts. House to house survey was done for collecting data on IDRS with pretested questionnaire. Cohen’s perceived stress scale was used to assess the level of stress. Results: Out of 200 study subjects, 53.5% were males, mean age was 40.13±15 years and 23% were illiterate. The overall prevalence of diabetes was 21.0%, as per IRDS, 20.5% were in low-risk category. 44.5% and 31.5% were in moderate and high-risk category respectively. No physical exercise- 45 (71.7%), consumption of non-vegetarian food- 43 (65%), low consumption of fruits- 47 (74.6%) among high-risk category. Sensitivity of IDRS was 50.6%, specificity 71.6%, positive predictive value 33.8% and negative predictive value 86.3%. Mean perceived stress score was found to be 19.5±4.03. Conclusions: This study estimated the usefulness of Indian diabetes risk score for identifying high risk diabetic subjects in Indian urban population so that proper intervention can be done to reduce the burden of disease. Stress may be included in the IDRS.